A new species of Renealmia (Zingiberaceae) from Colombia - Ospina, Juan C.; Pozner, Raúl E. (Phytotaxa, 2013)
Renealmia elianae (Zingiberaceae), a new species from the Central Andes of Colombia is described and illustrated. Renealmia elianae is morphologically close to R. puberula, differing by the inflorescence position, corolla size, labellum texture, surface and color, and size of the epigynous glands.